Factors associated with intention to use hormone replacement therapy among Thai middle-aged women - Montarat Burusanont (2018)
Objectives: To examine the differences among those who express their intentions to use hormone replacement therapy (intenders), those who express their intentions not to use hormone replacement therapy (non-intenders), and those who are undecided, and to examine the factors associated with hormone replacement therapy (HRT) intention among Thai middle-aged women. Methods: A total of 420 women aged 40-59 years, recruited from one hospital in Bangkok were asked to complete a self-administered questionnaire. Results: Compared to intenders and non-intenders, the undecided were significantly less knowledgeable about menopause and HRT, and perceived the highest level of decisional uncertainty. Being inadequately informed was the most important factor that distinguished the undecided from intenders and non-intenders. When looking at intenders and non-intenders, no significant differences in perceived information inadequacy, level of knowledge, and perceived risks of HRT were found. However, it was found that intenders perceived higher benefit over risk of HRT (OR=1.05, 95% CI=1.02, 1.07), held more negative beliefs towards menopause (OR=1.61, 95% CI=1.03, 2.53), and were approximately two times more likely to have ever used oral contraceptives (OR=1.99, 95% CI=1.13, 3.47) than non-intenders. Conclusion: The findings reveal the importance of being informed about menopause and HRT in making decision about HRT use. Changes in knowledge, and beliefs are promising avenues to study to see how these impacts HRT use. © 2003 Elsevier Ireland Ltd. All rights reserved.